Implementasi Layanan Bimbingan dan Konseling di Dunia Kerja - Ristianti, Dina Hajja (Attractive : Innovative Education Journal, 2022)
As a 21st century teacher, supervising teachers are required to have digital competence. Digital competence is the ability of a teacher to use information and communication technology based on pedagogical principles so that it has implications for methods in educating. This study wants to see the digital competencies possessed by supervising teachers. This study uses a quantitative descriptive method with a research sample consisting of 30 supervising teachers under the auspices of the Ministry of Religion of Rejang Lebong Regency. The data collection technique used a closed questionnaire which tabulated the responses to each item. The results of the tabulation are made into the average of the answers in each aspect. The results showed that the digital competence of teachers was in the medium category, where 40% of the responses were in the medium category. For this reason, supervising teachers need to be even more active to improve digital competence in the 21st century. Keywords: Counseling Services, Implementation Guidance & Counseling, Guidance and Counseling